The dead don't die [videorecording (DVD)] - Jarmusch, Jim, 1953-; Jarmusch, Jim, 1953-; Murray, Bill, 1950 September 21-; Driver, Adam; Waits, Tom, 1949- (Universal Pictures Home Entertainment, 2019)
The citizens of the small town of Centerville must battle for their survival when the dead begin to rise and attack them.